Intestinal herniation through anterior abdominal wall-sequalae of coffee machine burst: a rare case report and review of literature - Chand, Amar; Rajdev, Vivek; Sharma, Ankit; Chauhan, Arun; Sharma, Subhash (International Surgery Journal, 2022)
Evisceration of gut loops following blunt trauma abdomen leading to abdominal wall disruption is a rare entity. These injuries come under umbrella term of traumatic abdominal wall hernia (TAWH). The most common mode of trauma has been road side accidents. Many case reports of bicycle handle injuries leading to evisceration have been reported. But, TAWH occurring after injury due to explosion of household accessories has not been reported. The present case describes such condition and the management that followed.